Determinan Yang Mempengaruhi Profitabilitas Pada Perusahaan Transportasi Yang Listing di BEI Tahun 2020-2022 - Pertiwi, Dwi Ari; Agustina, Rachma; Ardiana, Meta; Humaidi; Husna, Lia Safarotul (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
The purpose of this study is to determine the effect of Institutional Ownership, Company Size and Liquidity on Profitability in Transportation Companies Listed on the IDX in 2020-2022. The type of research used in this study is quantitative research. The data collection technique used in this study is using secondary data. The population of this study was 27 companies and the sampling used in this study was purposive sampling so that 12 companies were obtained. Data analysis used the SPSS 20 software method. The results of this study indicate that Institutional ownership does not affect the Profitability of the annual report of transportation companies on the IDX in 2020-2022, this is indicated by a significant value of 0.556 meaning that the significant value is greater than 0.05. Company Size does not affect the Profitability of transportation companies on the IDX in 2020-2022, this is indicated by a significant value of 0.644 meaning that the significant value is greater than 0.05. Liquidity affects the profitability of transportation companies on the IDX in 2020-2022, this is indicated by a significant value of 0.000, meaning the significant value is less than 0.05.